INTEGRATING ARTIFICIAL INTELLIGENCE IN ISLAMIC RELIGIOUS EDUCATION: INNOVATION AND TEACHERS’ EPISTEMIC AUTHORITY - Ahmad Fauzi; Syukur Rahman; Zahara Zahara (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2026)
The integration of Artificial Intelligence (AI) into Islamic Religious Education (PAI) at Madrasah Ibtidaiyah offers opportunities for innovation while presenting ethical, pedagogical, and epistemic challenges. This study aims to analyze AI integration strategies and their implications for teachers’ epistemic authority and the integrity of Islamic values. A Systematic Literature Review approach guided by the PRISMA 2020 framework and thematic analysis was employed to examine literature meeting the selection criteria. The findings identify four major themes: AI-supported instructional strategies, preservation of teachers’ epistemic authority as murabbi, AI ethics and algorithmic bias, and the development of a value-oriented AI integration framework. AI can support learning personalization, instructional material development, and pedagogical decision-making; however, its implementation requires teacher validation, meaningful human oversight, and ethical consideration. This study proposes a conceptual framework integrating technological innovation, the murabbi concept, AI ethics, and maqāṣid al-sharī‘ah to promote responsible, contextually appropriate AI implementation aligned with the objectives of Islamic education.